The effect of commercial herbicide and bioherbicide of Ketapang (Terminalia catappa L.) on germination and chlorophyll content of cayenne pepper (Capsicum frutescens L.) - Rita Ariyana Nur Khasanah; Silvia Rahmawati (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
Herbicides that have less impact on non-target crops are better suited for weed control. The use of a commercial glyphosate-based herbicide (Roundup®) is a farmer's choice for controlling these weeds. The negative effects of glyphosate residues on cultivated crops, environment and human health have led farmers to switch to use bioherbicides. Ketapang (Terminalia catappa L.) leaves have been studied having the potential as bioherbicide but their effects on non-target plant have been less studied. This study aimed to examine the effects of Roundup® and Ketapang leaf extract on germination and chlorophyll content of cayenne pepper as non-target plant. This experimental study was conducted using completely randomized design (CRD) with 3 replications. Cayenne pepper was sown for 14 days. Parameters observed were germination, morphology, weight, and chlorophyll content of cayenne pepper sprouts. The data were analyzed using SPSS ver. 16 and tested with One-Way ANOVA or Kruskal Wallis tests at p-value of 0.05 depended on parametric assumption tests. There were significant differences between the Roundup® solution treatment with the control on all parameters (germination parameters, weight, and chlorophyll content of cayenne pepper sprouts) (p<0.05). The effect was getting worse seen in cayenne pepper seeds given high doses of Roundup® solution. On the contrary, there were no significant differences between the treatments of the aqueous extract of Ketapang leaves with the control on all parameters (p>0.05), except the vigor index. There were morphological changes in the radicle and root of cayenne pepper sprouts exposed to them. Rotted radicles were highly visible in Roundup®-exposed sprouts.